Hyaloklossia Labbé, 1896 (Alveolata: Apicomplexa) in frogs: Description of a new species and proposing a new subfamily to accommodate these enigmatic parasites. (August 2021) - Tokiwa, Toshihiro; Chou, Shyun; Tochigi, Yuki; Katayama, Kentaro; Duszynski, Donald W.
Abstract: Hyaloklossia Labbé, 1896 (Alveolata: Apicomplexa) is a monotypic genus of renal coccidia found in anurans, particularly in the edible frog Pelophylax kl. esculentus (Amphibia: Anura: Ranidae), distributed in different parts of Europe. Here we propose a new Hyaloklossia species from the Tokyo daruma pond frog, Pelophylax porosus porosus . The coccidium detected in the renal tissue of P. p. porosus shared some morphological characteristics with the type species, Hyaloklossia lieberkuehni (Labbé, 1894), reported from P. kl. esculentus . However, in addition to size differences in several oocyst and sporocyst features between these parasites, phylogenetic analysis of gene fragments from two nuclear ribosomal loci and the mitochondrial cytochrome c oxidase subunit 1, exposed distinct genetic differences between H. lieberkuehni and our new species. Although our analysis validated the monophyly of Hyaloklossia with some members of the Toxoplasmatinae Biocca, 1957, Cystoisosporinae Frenkel et al., 1987, and Eumonosporinae Chou et al., 2021 (Sarcocystidae Poche, 1913), comparison of genetic differences between Hyaloklossia species from P. p. porosus and H. lieberkuehni revealed the presence of a greater number of polymorphisms than that observed when comparing inter-species ( Heydornia spp., Besnoisita spp.) or inter-genus ( Toxoplasma vs . Neospora, Neospora vs. Hammondia, and Neospora vs . Heydornia ) variabilities among members of the Sarcocystidae. This indicates that Hyaloklossia, as re-erected and defined by Modrý et al. (2001, Int. J. Syst. Evol. Microbiol. 51, 767–772), with its homoxenous life cycle, requires placement in its own subfamily. Thus, we propose a new subfamily, Hyaloklossiinae n. subfam., to accommodate two species, H. lieberkuehni from Europe and Hyaloklossia kasumienesis n. sp. which we describe here from P. p. porosus in Japan. Graphical abstract: Image 1 Highlights: Hyaloklossia was detected from the kidney of Pelophylax porosus porosus (Amphibia: Anura). The species was described as Hyaloklossia kasumiensis n. sp. This is a new host record for Hyaloklossia and also the first report in Asia. Hyaloklossiinae, was proposed as a new subfamily in the Sarcocystidae.